1999
DOI: 10.4141/p98-132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barley plant density on wild oat interference, shoot biomass and seed yield under zero tillage

Abstract: . 1999. Effect of barley plant density on wild oat interference, shoot biomass and seed yield under zero tillage. Can. J. Soil Sci. 79: 655-662. There has been little research aimed at developing regression models to describe the effects of barley and wild oat plant density on barley yield loss, or wild oat biomass and seed yield. Such models are an important component of integrated weed management systems, and can help determine when weed control with herbicides is economical. Field experiments were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 20 publications
5
52
1
Order By: Relevance
“…In many studies, the effect of weed interference on kernel weight in wheat has been non-significant (Satorre and Snaydon 1992;Hucl 1998;Das and Yaduraju 1999;Welsh et al 1999). Satorre and Snaydon (1992) reported similar results for the yield components of wheat, oat and barley under competition from Avena fatua L.; however, O'Donovan et al (1999) reported that competition from A. fatua L. caused marginal decreases in the kernel weight of barley. Satorre and Snaydon (1992) suggested that the lack of change in kernel weight as a result of competition may be related to the timing of weed competition.…”
Section: Competitive Ability In Grain Cropsmentioning
confidence: 59%
See 1 more Smart Citation
“…In many studies, the effect of weed interference on kernel weight in wheat has been non-significant (Satorre and Snaydon 1992;Hucl 1998;Das and Yaduraju 1999;Welsh et al 1999). Satorre and Snaydon (1992) reported similar results for the yield components of wheat, oat and barley under competition from Avena fatua L.; however, O'Donovan et al (1999) reported that competition from A. fatua L. caused marginal decreases in the kernel weight of barley. Satorre and Snaydon (1992) suggested that the lack of change in kernel weight as a result of competition may be related to the timing of weed competition.…”
Section: Competitive Ability In Grain Cropsmentioning
confidence: 59%
“…1996;Champion et al 1998;Weiner et al 2001) and barley (O'Donovan et al 1999). Champion et al (1998) found that in wheat, this was true up to a certain density, after which no yield increases were seen.…”
Section: Breeding For Competitive Abilitymentioning
confidence: 99%
“…Increasing crop seeding rates was also shown to reduce weed competition and thus reduce weed seed production and its negative impact on yields of wheat (Carlson and Hill 1985) and barley (Evans et al 1991;Barton et al 1992;Kirkland 1993;O'Donovan et al 1999). Conceivably, selecting competitive cereal varieties and seeding them at relatively high seeding rates would contribute to the development of more economical and sustainable cropping systems by reducing dependence on herbicides for weed control.…”
Section: Mots Clés: Blé Roux Vitreux De Printemps (Brvp) Blé De Prinmentioning
confidence: 99%
“…Crop density has also been shown to have a major influence on yield losses caused by weeds in barley (O'Donovan et al 1999), wheat (Carlson and Hill 1985) and canola (O'Donovan et al 1988(O'Donovan et al , 1989. Relationships between observed and estimated crop yield loss were generally superior in barley and canola when this function was included in the equations compared to weed density alone (Figs.…”
Section: Discussionmentioning
confidence: 92%
“…In later studies, more complex equations were developed to include the relative time of emergence of wild oat and crop (Cousens et al 1987) or crop density (O'Donovan et al 1999) in addi-tion to wild oat density. Regression equations were also developed for estimating canola yield losses due to volunteer barley (O'Donovan et al 1988) and wheat (O'Donovan et al 1989).…”
Section: Mots Clésmentioning
confidence: 99%